Catch Rate and Fish Catch of Boat Lift Net on Different Position in Palabuhanratu Bay Water, Sukabumi, Indonesia - Izza Mahdiana Apriliani; Indah Riyantini; Emma Rochima; M Fahmi Ikmal (Jurnal Perikanan dan Kelautan, 2018)
The waters of Palabuhanratu Bay known as the main fishery base in Southern Java Indonesia because dynamical of oceanography influenced by the Indian Ocean. The common fishing gear used in these waters is the lift net, utilizing the phototactic properties of the fish. To determine the catch rate of lift net, focus of this study is to assess the catches with two different fishing areas of lift net with the coordinates of 07° 00' 00.6" S and 106° 32' 12.1" E (near from coast); 06° 59' 57.7" S and 106° 31' 39.7" E (far from coast). Catch rate analysis used Shindo's formulation interpretation, with the required data being the catch and effort. Captures near and far are dominated by Hairtail Fish weighing 3,3 - 38,5 kg with average catch weight for each trips ranging from 12,1 - 12,8 kg. The catch rate patterns for each type of fish did not differ significantly, the maximum value is Hairtail Fish on the far lift net and the minimum value is Mysis in the near lift net, and both lift nets have the same catch rate for the Squid and Seed Mackerel species. The main catch rate for the near lift net is 0,09 kg/h and for the 0,19 kg/h far lift net, while the side catch rate for the lift net is 2,21 kg/h and the chart is 2,45 kg/h.